Upaya Meningkatkan Pelayanan untuk Mencapai on Time Performance pada Petugas Check in Counter Maskapai Batik Air di Bandar Udara Jenderal Ahmad Yani Semarang - Novie Triyani Agustin; Hodi (MES Bogor, 2024)
Punctuality for airport officials, especially On Time Performance (OTP) which is an important factor that must be fulfilled in air transportation activities, if On Time Performance (OTP) is not achieved, it will have various impacts. One of the units responsible for the smooth running of passengers is check-in Counter. This study discusses the obstacles of officers and solutions that can be done so that there are no delays in the unit Check-In in creating On Time Performance in flight. The research method used is a descriptive qualitative method. The collection of research data was carried out by means of interviews, observations, documentation and literature studies in the Check In Counter work unit area of Jenderal Ahmad Yani Airport Semarang. Based on the research findings, there are challenges faced by the check-in counter staff in achieving On Time Performance (OTP) for Batik Air at Jenderal Ahmad Yani International Airport in Semarang. These challenges are divided into two factors: internal and external. The internal factors include system server check-in failures and insufficient time allocated for the check-in process. Meanwhile, external factors involve passengers who cannot present valid identification, those arriving at the last minute, or passengers who are late for check-in. To address these issues and improve OTP, Batik Air has taken measures by ensuring that check-in counter personnel meet the required criteria and possess the necessary competence to follow the established standard operating procedures. Additionally, check-in staff are trained to be friendly, responsive, and prioritize passengers who are already in line, especially those arriving 15 minutes before the check-in counter closes.